A Narrative Analysis Examining Influential Factors of a Minority Research and Training Program. (August 2021) - Burton, Gretchen S.; Vicente, Maria da Graça H.
The implementation of minority research and training programs at the postsecondary level has risen to close the educational achievement gap and generate a highly skilled and diverse science workforce. Numerous studies identify interventions influencing positive outcomes among minority research and training participants achieving graduate degrees. However, many of these studies utilize quantitative methods. To capture student voices and rich descriptive experiences, this study utilized a multiple case study featuring a narrative approach. Cross-case analysis identified four factors influencing matriculation into advanced degree programs: belonging and inclusion, peer mentoring, confidence as a scientist, and family influence. Findings from this study expand the current body of knowledge and provide implications for practice to better serve underrepresented students in the science, technology, engineering and mathematics disciplines.